Study on antimicrobial usage and awareness on antimicrobial resistance among small ruminant farmers in Ladang Angkat Farms, UPM, Selangor, Malaysia - Siti Farahani binti Khalid (2017)
Recent trends on the use of antimicrobials have become an alarming risk factor for antimicrobial resistance (AMR) in ruminant farming. Demand for antimicrobials usage (AMU) in livestock production can be affected by farmer’s knowledge, attitude and practices. A cross-sectional study involving small ruminant farmers in Ladang Angkat Programme, UPM, in Selangor area was conducted to assess their practices on antimicrobial usage; as well as to evaluate their understanding and awareness on AMR. A total of 13 respondents, from 9 small ruminant farms were enrolled in this study. Questionnaires comprised of five sections: the demographic characteristics, general management of the farm, assessment on knowledge and practices on AMU and AMR. Result indicated that these farms acquire 3 to12 types of antimicrobial drugs with penicillin (41%) and tetracyclines (36%) being the most common antibiotics used. Generally, respondents were found to have sufficient knowledge on certain aspects on antimicrobials usage but not in their practices. About 54% of the respondents did not understand the actual scenario regarding AMR and its impact contributed from the livestock farming. Results were also suggestive that there was an association between the level of education and work position of the respondents and their awareness on AMR (P<0.05). Result suggested that there is lack of awareness on AMR among farmers as majority of them were not aware on the prudent use of antimicrobials, thus increasing awareness on AMR through guidance and education to the farmers are greatly warranted.